PENGARUH BENDING PADA ANTENA MIKROSTRIP TERHADAP POLA RADIASI DAN POLARISASI DENGAN ORIENTASI BENDING ARAH SUMBU Y - Faizal Reza; Muhammad Fauzan Edy Purnomo; Ali Mustofa (Jurnal Mahasiswa TEUB, 2023)
Antennas are expected to keep up with an era that requires flexible and wearable forms. In this use, it is possible to require bending of the microstrip antenna which changes the characteristics or parameters. In this research a microstrip antenna is designed with a 30-star ground plane patch in the form of a staircase working at a frequency of 2.4 GHz. Design and simulation were carried out in CST Studio Suite 2018 software and measurements were carried out with a Signal Generator and SpectrumAnalyzer. The simulation results show that bending causes yield degradation only in the parameters of the microstrip antenna, which is axial ratio that has an impact on polarization. And the measurement results show that there is degradation only in the axial ratio parameter which affects polarization. The smaller the bending radius that is done so that the antenna bends more, the way the antenna works will change. Keywords: Microstrip Antenna, Bending, Radiation Pattern, Polarization, Axial Ratio